P410 Safety of biological drugs for inflammatory bowel disease in elderly patients. (21st January 2022) - Suarez Ferrer, C J; Mesonero, F; Caballol, B; Ballester, M P; Baston Rey, I; Castaño Garcia, A; Miranda Bautista, J; Saiz Chumillas, R; Benitez, J M; Sanchez Delgado, L; Lopez-Garcia, A; Rubin de Celix, C; et al.
Abstract: Background: The most feared adverse events related to biological treatment in patients with inflammatory bowel disease (IBD) are the development of tumors and / or serious infections. These events are generally more frequent in elderly patients, so the increased use of biological drugs in these patients today makes it necessary to assess the safety of these drugs in this population. Methods: Patients have been retrospectively included with established diagnosis of IBD at age, 65 at the time of initiating biological treatment(Infliximab, Adalimumab, Golimumab, Ustekinumab or Vedolizumab).Data regarding the development of oncological events during treatment have been collected. Variables related to infectious processes during biological treatment have also been included, documented by microbiological analysis and requiring systemic treatment and / or hospitalization(excluding bowel infection by CMV). Statistical analysis was performed with Stata, 15.0, categorical variables were compared with the chi2 test for proportions Results: 1090 patients have been retrospectively included. Regarding the development of tumors, we observed an oncological event in, 74 (6.9%). They developed in, 30 patients (8%) with infliximab, 23 patients (7.1%) with adalimumab, 3 patients(11.1%) with golimumab, 10 patients (6.4%) with ustekinumab, and, 8 (3, 8%) vedolizumab. It was significantly lower(p = 0.04) for the vedolizumab group compared to other treatments, however, statistical significance was not reached for the ustekinumab group (p = 0.5)., 31% (23 patients) had an oncological history prior to the start of the biological treatment under study. The most frequently developed tumors were cutaneous, not melanocytic in, 10 patients, lung in, 10 patients and hematological tumors (7 non-Hodgkin lymphoma, 3 acute leukemias and, 2 intestinal lymphomas), 7 bladder tumors, 5 prostate and, 4 colorectal carcinoma.Regarding the development of infections, these occurred in, 160 patients during biological treatment(14.9%), without differences between the different biological drugs used (p = 0.61): infliximab, 61, (19.4%), adalimumab, 39 (12.5%), golimumab, 5(17.8%), ustekinumab, 22(14.1%), and vedolizumab, 34 (16.5%).Likewise, 85 (53.1%) require hospitalization due to the infectious process and in, 51(31.9%), it is permanently suspended due to the infection.Until the end of the follow-up, 158 patients (36.4%) suspended the biological drug due to an adverse effect, with the time until suspension:, 1.47 years(mean); SD:1.6 Conclusion: In our experience, the development of tumors is more frequent in patients who use anti-TNF compared to other targets, although its incidence is generally low. However, there are no differences in the development of infections between the different biological treatments.